PERBANDINGAN METODE COILED TUBING DAN PUMP PADA APLIKASI SOLVENT TREATMENT BERDASARKAN PARAMETER SUCCESS RATIO DAN CUT OFF DI LAPANGAN FASH - Melysa, Richa; Anwar, Irwan; Sulistya, Jehan; Afdal, Afdal (ITP Press, 2024)
The Fash field is a heavy oil category managed by PT. Chevron Pacific Indonesia with sandstone rock type. So that along with the production of oil to the surface, there will be production problems such as asphaltene. To overcome the problem of asphaltene, a solvent is used to dissolve asphaltene in the form of a solvent. There are 2 methods used to perform solvent injection, namely by using a coiled tubing and by using a pump. This research will discuss the success rate of each method in the solvent treatment application and the determination of the threshold value in order to determine the right candidate well for each method of use. In determining the level of success, Minimum oil recovery for each method, namely coiled tubing and pump is 8 bopd and 4 bopd and to determine the threshold value, a parameter that has a certain value is used as a reference to maximize the use of existing methods in solvent treatment applications. The parameters used are asphaltene content (%), water cut (%), wellhead temperature (°F), and reservoir temperature (°F).